(3x-8)(8x+7)=

Simple and best practice solution for (3x-8)(8x+7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-8)(8x+7)= equation:


Simplifying
(3x + -8)(8x + 7) = 0

Reorder the terms:
(-8 + 3x)(8x + 7) = 0

Reorder the terms:
(-8 + 3x)(7 + 8x) = 0

Multiply (-8 + 3x) * (7 + 8x)
(-8(7 + 8x) + 3x * (7 + 8x)) = 0
((7 * -8 + 8x * -8) + 3x * (7 + 8x)) = 0
((-56 + -64x) + 3x * (7 + 8x)) = 0
(-56 + -64x + (7 * 3x + 8x * 3x)) = 0
(-56 + -64x + (21x + 24x2)) = 0

Combine like terms: -64x + 21x = -43x
(-56 + -43x + 24x2) = 0

Solving
-56 + -43x + 24x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-7 + -8x)(8 + -3x) = 0

Subproblem 1

Set the factor '(-7 + -8x)' equal to zero and attempt to solve: Simplifying -7 + -8x = 0 Solving -7 + -8x = 0 Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -8x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -8x = 0 + 7 -8x = 0 + 7 Combine like terms: 0 + 7 = 7 -8x = 7 Divide each side by '-8'. x = -0.875 Simplifying x = -0.875

Subproblem 2

Set the factor '(8 + -3x)' equal to zero and attempt to solve: Simplifying 8 + -3x = 0 Solving 8 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -3x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -3x = 0 + -8 -3x = 0 + -8 Combine like terms: 0 + -8 = -8 -3x = -8 Divide each side by '-3'. x = 2.666666667 Simplifying x = 2.666666667

Solution

x = {-0.875, 2.666666667}

See similar equations:

| 4a-13=-8 | | 1/4(y+4)=3 | | 11x+22=5x+184 | | 1.4u-1.2=0.1u-5.1 | | 3(4x-10)=6x-60 | | 3(x-2)+2(x+5)=2[x+(2x-1)] | | 9x+13=6x+2 | | -1/8(z-6)=-3/4(z-1/9) | | -1/2(z+1/9)=-3/8(z+1/2) | | 3+6n=7n-5 | | g(x)=x^2-2x-5 | | 1000+700+6x=800+300+8x | | 117-7x=29x+17 | | 7y+21=5 | | -2w-17=4w+19 | | 2/12+3/4 | | 8(2x+5)=3(x+4)+2 | | 7x-2(5-x)=3+2x+1 | | 5*12+13+3*14+2*15+4*16+17+19+3*20/20 | | 12-8m=2m+2 | | 14-(2q+5)=(-2q)+9 | | -3/4x+5/4=x+3 | | 12x+4/4(x-1)(x+1)=5/4 | | 8x-16=4(2x-4) | | 22=4+3t | | x+30=93 | | -1/4y+5/4=-5/6y+5/3 | | -42=14y | | .2x-3=1 | | -5(9r+10)+5r=10(r+10) | | 2.2x-3=1 | | 3r^2+10r-4=84 |

Equations solver categories